Apathy in Essential Tremor, Dystonia, and Parkinson's Disease: A Comparison with Normal Controls - Louis, Elan D. (2011)
BACKGROUND: Apathy, defined as decreased goal-directed activity, has been observed in Parkinson's disease. A number of cognitive/psychiatric features have been documented in essential tremor, yet we are unaware of studies of apathy. METHODS: Using the Apathy Evaluation Scale (range = 18–72 [more apathy]), we compared 79 essential tremor cases, 20 dystonia cases, and 39 Parkinson's disease cases with 80 normal controls. RESULTS: The score of the Apathy Evaluation Scale was higher in essential tremor, dystonia, and Parkinson's disease cases than controls (all P ≤ .04). Parkinson's disease cases had the highest scores. Analyses stratified by presence/absence of depressive symptoms indicated the presence of a group of apathetic but nondepressed cases. CONCLUSIONS: Patients with Parkinson's disease, essential tremor, and dystonia had elevated apathy scores. Features of apathy seemed to occur in these conditions independent of depressive symptoms. The mechanistic basis for the apparent increased features of apathy in essential tremor and dystonia deserves further study.